Epidemiology of uterine fibroids - Knapp, Paweł; Chabowski, Adrian; Knapp, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
Uterine fibroids are the most common benign tumors of the female genital tract. However, true epidemiological data analyzing the incidence rate are still under-estimated. This is because fibroids remain undiagnosed since most of them are asymptomatic and confirmed during a histology examination after hysterectomy. Uterine fibroids are clinically apparent in up to 25% of all women and up to 30-40% of women over 40 years of age. Several risk factors have been identified, such as ethnicity, nulliparity, hormonal factors and genetics. Several epidemiological data have also demonstrated that the incidence of uterine fibroids is higher in blacks than in whites. Although the etiology of uterine fibroids is unknown, there have been some major advances in understanding the pathogenesis of this condition. This paper presents current knowledge of epidemiology of uterine fibroids.